Generalized theory of thermoelastic diffusion with double porosity - Kansal, T. (Archives of Mechanics, 2018)
The present paper focuses on the derivation of the constitutive relations and field equations for anisotropic thermoelastic medium with mass diffusion and double porosity. The variational principle, uniqueness and reciprocity theorems are also derived.